Social and cultural influences on tobacco-related health disparities among South Asians in the USA. Issue 4 (27th June 2011) - Mukherjea, Arnab; Morgan, Patricia A; Snowden, Lonnie R; Ling, Pamela M; Ivey, Susan L
Abstract : Objective: To explore and understand key cultural contexts of tobacco use among South Asian communities in the USA. Design: Focus groups, with homogeneous compositions of gender, generational status and length of time in the USA, were conducted in two distinct South Asian ethnic enclaves. Focus group findings were triangulated with observational data regarding the availability of culturally specific tobacco from commercial ethnic outlets and cultural events. Subjects: Respondents included 88 men and women of South Asian descent, aged 18–65 years, immigrant and native born, representing diversity of religion, socioeconomic status and region of origin, with the use of at least one culturally specific tobacco product in previous 24 months. Results: A large number of culturally specific products were commonly used by community members. Knowledge of product-specific health risks was lacking or inaccurate. Many culturally specific tobacco products were considered to have beneficial properties. South Asian tobacco items were used to preserve cultural traditions and express ethnic identity in a new dominant culture. The social and cultural values ascribed to use helped distinguish community members from mainstream society and from other minority populations. Conclusions: Many cultural factors govern tobacco use among diverse global populations. Especially for migrants with a common regional origin, the role of ethnic identity may strongly influence culturally specific tobacco patterns. Qualitative inquiry helps elucidate such culturally framed behaviour in culturally diverse populations. These cultural contexts should be integrated into research and practice. Understanding multidimensional factors influencing non-traditional tobacco use is essential to ensure that comprehensive tobacco control strategies address tobacco-related disparities.